Estudo numérico dos efeitos das zonas climáticais locais e infraestruturas verdes nas variáveis atmosféricas para a região metropolitana de Londrina - Medeiros Sobrinho, Otavio (2021)
Urban areas concentrate more than 50% of the world's population and are highly impacted by human activities. In this sense, Green Infrastructures (GIs) are used to mitigate these effects. Atmospheric models, such as the Weather Research and Forecasting with Chemistry (WRF-Chem), represent the mesoscale meteorological variables numerically. Information involving urban structures is a gap that makes it difficult to numerical reproduce turbulent flows, mainly in urban areas. To overcome this limitation, the classification of Local Climate Zones (LCZs) makes it possible to obtain a product with 10 classes (31 to 40) representing the urban structures defined according to similar surface properties. Thereby, this work evaluated the effects on meteorological variables and on air quality using WRF-Chem with the urban classes of LCZs in the land use for the Metropolitan Region of Londrina well as the implementation of GIs distributed in the urban area. The LCZs were obtained from the supervised classification of Landsat 8 satellite images using SAGA GIS and Google Earth Pro. The model simulations were configured in 3 domains with 100 x 80, 88 x 70, and 76 x 58 points (9 km, 3 km, and 1 km of grid spacing). Additionally, five urban parks and two urban lakes were identified and expanded in a fourth nested grid with 0.333 km grid spacing to analyze environmental systems' meteorological effects on the urban environment. The quantitative verification was carried out using statistical indexes to analyze model performance in the region's current conditions. Two meters Air temperature (T2) and specific air humidity (Q2) are best represented for both monitoring stations (Instituto Água e Terra - IAT and Sistema de Tecnologia e Monitoramento Ambiental do Paraná - SIMEPAR) when using an LCZs (World Urban Database and Access Portal Tools - WUDAPT), compared to the default land use file (Moderate - Resolution Imaging Spectroradiometer - MODIS). The WS10 at the IAT station presents improvement for all statistical indices due to the better vertical representation of urban structures by LCZs. For the pollutants, there was no statistical improvement. The lake had no relevant effect on meteorological variables, probably due to horizontal dimensions. The parks, in addition to contributing locally to the reduction of the effects of the Urban Heat Island (UHI), presented cooling rates and increased in Q2 in up to six grid points, approximately 2 km, around these infrastructures, performing environmental services to mitigating the effects of UHI sustaining the importance of these systems in urban projects. In general, the use of LCZs improved the performance of the model to represent meteorological variables. The GI showed benefits for the local climate even in medium-sized cities.